Strategi Penciptaan Kelas yang Kondusif Melalui Penguatan Iklim Kelas, Komunikasi Efektif, dan Teknik Motivasi Belajar - Mahfudliyah Mahfudliyah; Indah Nurmaasari; Safira Anisa Rahman; Laailatul Usriyah (Jurnal Ilmiah Literasi Indonesia, 2026)
This study discusses classroom management strategies to create a conducive learning atmosphere through three main elements: strengthening the classroom climate, effective communication, and learning motivation techniques including ice-breaking. A conducive classroom environment significantly helps students focus on absorbing lessons, enhances academic and social development, and optimizes learning outcomes. Conversely, unmanaged classroom conditions impede teaching and learning processes while diminishing students' enthusiasm. Through optimal classroom climate management, professional educator interaction, structured communication, and psychological approaches like positive reinforcement and refreshing ice-breakers, an active, effective, and joyful learning environment (PAKEM) can be successfully established.